NEW INSIGHTS INTO PEER FEEDBACK IN VIRTUAL LANGUAGE EXCHANGES - Iglesias, Montserrat; Tarazona, Cristina (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
To foster the acquisition of English or Spanish as a foreign language, 26 undergraduate students took part in a synchronous virtual language exchange between Oxford College of Emory University (United States) and CETT Barcelona School of Tourism, Hospitality and Gastronomy (affiliated with the University of Barcelona, Spain). After each conversation, participants had to fill in a 5-item questionnaire and comment on their language partner’s performance. Individual feedback was gathered by means of Google Forms and referred to overall oral performance, specific grammar and vocabulary errors, specific pronunciation errors, improvement suggestions for enhanced communication, and remarkable conversation features. To explore the main characteristics and components of peer feedback in this virtual context, the comments provided by the participants were analysed through content analysis and categorization using the qualitative data analysis software QDA Miner Lite. The results show that the participants made constructive recommendations and comments that supported the development of their communicative competences and intercultural skills. In practical terms, the specific strengths and weaknesses pointed out in the questionnaires can be used as formative indicators by students and instructors. This small-scale study aligns with previous research indicating that peer feedback as an integrated element in virtual language exchanges contributes to linguistic awareness and progress among undergraduate foreign language learners.